Bridging gender gaps in rangeland resource and conflict mapping: the role of participatory GIS, a case study in Kenya - Paliwal, Ambica; Korir, Victor Kipkurui; Kenduiywo, Benson; Galiè, Alessandra; Bullock, Renee; Pacillo, Grazia; Wane, Abdrahmane; Whitbread, Anthony M. (International Rangeland Congress, 2025)
The study explores the role of Participatory Geographic Information Systems (PGIS) in resource mapping, policy development, and conflict resolution in Isiolo County, Kenya. By integrating Traditional Ecological Knowledge (TEK) with modern mapping, PGIS enhances accuracy and community engagement. The approach emphasizes gender inclusion, with men identifying broader features and economic resources, and women highlighting water access and household needs. Gender-specific maps improve equity in resource management. PGIS also helps resolve rangeland conflicts by mapping contested areas and facilitating inter-community dialogue. Using Focus Group Discussions and Key Informant Interviews, the study captures diverse local insights on environmental challenges and climate impacts. The findings underscore PGIS as a vital tool for sustainable rangeland governance, promoting resilience, inclusivity, and informed policymaking.